Endothelial sprouting and network formation in collagen- and fibrin-based modular microbeads. (1st January 2016) - Rioja, Ana Y.; Tiruvannamalai Annamalai, Ramkumar; Paris, Spencer; Putnam, Andrew J.; Stegemann, Jan P.
Graphical abstract: Abstract: A modular tissue engineering approach may have advantages over current therapies in providing rapid and sustained revascularization of ischemic tissue. In this study, modular protein microbeads were prepared from pure fibrin (FIB) and collagen–fibrin composites (COL–FIB) using a simple water-in-oil emulsification technique. Human endothelial cells and fibroblasts were embedded directly in the microbead matrix. The resulting microbeads were generally spheroidal with a diameter of 100–200 μm. Cell viability was high (75–80% viable) in microbeads, but was marginally lower than in bulk hydrogels of corresponding composition (85–90% viable). Cell proliferation was significantly greater in COL–FIB microbeads after two weeks in culture, compared to pure FIB microbeads. Upon embedding of microbeads in a surrounding fibrin hydrogel, endothelial cell networks formed inside the microbead matrix and extended into the surrounding matrix. The number of vessel segments, average segment length, and number of branch points was higher in FIB samples, compared to COL–FIB samples, resulting in significantly longer total vessel networks. Anastomosis of vessel networks from adjacent microbeads was also observed. These studies demonstrate that primitive vessel networks can be formed by modular protein microbeads containing embedded endothelial cells and fibroblasts. Such microbeads may find utility as prevascularized tissue modules that can be delivered minimally invasively as a therapy to restore blood flow to ischemic tissues. Statement of significance: Vascularization is critically important for tissue engineering and regenerative medicine, and materials that support and/or promote neovascularization are of value both for translational applications and for mechanistic studies and discovery-based research. Therefore, we fabricated small modular microbeads formulated from pure fibrin (FIB) and collagen–fibrin (COL–FIB) containing endothelial cells and supportive fibroblasts. We explored how cells encapsulated within these materials form microvessel-like networks both within and outside of the microbeads when embedded in larger 3D matrices. FIB microbeads were found to initiate more extensive sprouting into the surrounding ECM in vitro . These results represent an important step towards our goal of developing injectable biomaterial modules containing preformed vascular units that can rapidly restore vascularization to an ischemic tissue in vivo .